2005
DOI: 10.1177/106689690501300210
|View full text |Cite
|
Sign up to set email alerts
|

So-Called “Inflammatory Leiomyosarcoma”: A Series of 3 Cases Providing Additional Insights into a Rare Entity

Abstract: Inflammatory leiomyosarcoma, a rare entity first described in 1995, has been characterized by smooth muscle differentiation, a near-haploid karyotype, and a surprisingly good prognosis. The morphology is similar to that of conventional leiomyosarcoma admixed with a chronic inflammatory infiltrate. Thus far, only 15 cases have been reported in the English language literature. We report the clinical and pathological features of 3 additional cases of inflammatory leiomyosarcoma. Two women (ages 64 and 25, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 30 publications
6
55
0
Order By: Relevance
“…The latter are known to show only focal expression of actin and/or h-caldesmon, yet significant reactivity for desmin. 21,22 Out of the five markers covered in this study, only h-caldesmon appears to be specific to true smooth muscle differentiation, confirming the results of previous studies. 6,7 Actin is nonspecific and is found in a subset of rhabdomyosarcomas, 23,24 and in one pleomorphic rhabdomyosarcoma in this study.…”
Section: Se Of Smooth Muscle Markers For the Diagnosis Of Leiomyosarcsupporting
confidence: 89%
“…The latter are known to show only focal expression of actin and/or h-caldesmon, yet significant reactivity for desmin. 21,22 Out of the five markers covered in this study, only h-caldesmon appears to be specific to true smooth muscle differentiation, confirming the results of previous studies. 6,7 Actin is nonspecific and is found in a subset of rhabdomyosarcomas, 23,24 and in one pleomorphic rhabdomyosarcoma in this study.…”
Section: Se Of Smooth Muscle Markers For the Diagnosis Of Leiomyosarcsupporting
confidence: 89%
“…Including the 4 new cases presented here, there are now 10 reported inflammatory leiomyosarcomas with confirmed near-haploidization (refs 2-4 and present study), the clinical features of which seem to be distinct from those in other forms of leiomyosarcoma. First, there is a skewed sex distribution, with only one woman among the inflammatory leiomyosarcoma cases; 4 this feature was not observed in the first report of inflammatory leiomyosarcoma. 1 Second, inflammatory leiomyosarcoma patients are younger, median age 41 years (range, 18-64 years), than conventional leiomyosarcoma patients.…”
Section: Discussionmentioning
confidence: 94%
“…In six of the cases, massive reduction of the chromosome number to a hyperhaploid level (25-28 chromosomes), with or without subsequent polyploidization, was found to constitute an early step in tumorigenesis. [2][3][4] Furthermore, the copy number distribution of individual chromosomes in inflammatory leiomyosarcoma is clearly nonrandom with all six cases with a hyperhaploid origin showing retained biparental disomy for chromosomes 5 and 22, and often also for chromosomes 18, 20, and 21. 2 Nord et al 2 also performed global gene expression analysis on 3 inflammatory leiomyosarcomas and 15 leiomyosarcomas and found that these tumors have distinct transcriptional profiles, and that genes located on the disomic chromosomes are expressed at higher levels than genes on the monosomic chromosomes.…”
mentioning
confidence: 96%
“…both chromosomes 12 with secondary duplication of the chromosome complement. The occurrence of near haploid karyotypes has been observed in a variety of solid tumors including leiomyosarcomas [7] as well as in leukemias [8]. Also, copy-number-neutral LOH affecting more or less large segments has been observed in many cancers [9].…”
Section: Discussionmentioning
confidence: 99%